2009
DOI: 10.1111/j.1523-536x.2009.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

“It's All the Rage These Days”: University Students' Attitudes Toward Vaginal and Cesarean Birth

Abstract: Results indicate that a preference for cesarean section is linked to fear of childbirth and driven by low confidence in vaginal birth. Educational strategies targeting university-aged men and women may be helpful in alleviating fears of vaginal birth and providing evidence-based information about different birth options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
5
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 23 publications
5
47
5
13
Order By: Relevance
“…In addition, the refinement and development of the CFPP scale was informed by quantitative and qualitative findings from a large sample of young women and men (14,15) thus enhancing the validity of items added to the scale. 16 …”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the refinement and development of the CFPP scale was informed by quantitative and qualitative findings from a large sample of young women and men (14,15) thus enhancing the validity of items added to the scale. 16 …”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Elevated risk perceptions were associated with increased fear of birth among men (15); when asked why young men and women preferred Cesarean section over vaginal birth, 56% of women and 32% of men chose CS to avoid labour pain and/or because they are afraid of pain (16). 6 This body of literature informed the development of a fear of childbirth measure for young women and men who plan to have children in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The original survey consisted of Likert type and open-ended questions such as 'please explain why you prefer vaginal birth/cesarean section'. A thematic analysis of the qualitative data [37] was used to inform response options and to develop additional questions in the current survey. For instance, pre-defined response options for why students prefer cesarean section or vaginal birth were based on recurring issues within the qualitative accounts.…”
mentioning
confidence: 99%
“…Studies regarding women's choices in giving birth have shown that fear of childbirth is an important factor in their choice of cesarean section [5][6][7][8][9][10][11]. A lack of knowledge about childbirth, a negative image of giving birth and incorrect information cause fear, and this leads to women requesting a cesarean birth [12].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of knowledge about childbirth, a negative image of giving birth and incorrect information cause fear, and this leads to women requesting a cesarean birth [12]. Other factors in the choice of a cesarean section are the idea that it is safer or healthier [7,9,10], avoiding damage to the body [6,9], the idea that it is safer for the baby [6,7], a recommendation by the doctor or midwife [8,13], planning the time of birth [8,10], and making a return to sexual activity easier [14] as well as if the doctor who is assisting at the birth is male [15].…”
Section: Introductionmentioning
confidence: 99%